Music Theory and the Epistemology of the Internet; or, Analyzing Music Under the New Thinkpiece Regime - O’Hara, William (Analitica. Rivista online di studi musicali, 2017)
The proliferation of online news and general interest websites (such as FiveThirtyEight, Slate, Vox, and others) over the past decade has centered around a particular genre of short-form expository writing, sometimes referred to as the "thinkpiece," "explainer," or "blessay" (blog + essay). These essays analyze and comment upon current events, politics, and popular culture, often from the perspective of statistics or behavioral psychology, and usually with the professed goal of exposing the hidden forces and structures at play in culture and society. Some such essays address music theory, often attempting to explain the popularity of a current pop hit by analyzing its harmony, rhythm, or structure. Music analyses in the popular online press exhibit several common traits in common. First, they reflect an interest in hermeneutics, often mapping musical structures onto political or cultural phenomena, illuminating a connection between some priorities of contemporary musicology, and those of society writ large. Second, they are often presented from a second-hand perspective: the journalists themselves are rarely musicians, instead reporting on the analyses of friends or colleagues, opening the door for simplifications and distortions. Finally, these popular essays mirror the tendencies of the neoliberal academy, instrumentalizing music theory by treating it as a monolithic, panstylistic tool that yields objective insight, rather than a multifaceted discipline that is deeply implicated with aesthetics, culture, history, and politics.